Perancangan Visual Karakter Mainan Boneka Fashion Sebagai Media Edukasi Pakaian Adat Suku Jawa Untuk Anak Usia Prasekolah - Wiedhella, Zahra Agnestia; Ayuswantana, Alfian Candra; Widyasari, Widyasari (Peneliti.net, 2024)
Indonesia is an archipelagic country that is rich in cultural diversity and has its own cultural characteristics in each tribe spread across various islands. Traditional clothing is one of the riches that Indonesia has which must be preserved by the nation's future generations. One of the main problems in the world of education is the lack of effective learning methods used by students. In improving the quality of education, innovation is needed in terms of student learning styles. Children not only sit quietly listening to lectures given by their teachers but they also actively interact with various materials, objects and other children around them. The development of dolls from time to time differs in terms of their physical form and function. Dolls in the current era have very broad functions seen from their physical form, ranging from accessories, furniture, toys, even learning media. The design of a doll design requires visual characters that have distinctive characteristics and personality, facial expressions to capture emotions, body language to convey a story or message.